Pilot study of fractional CO2 laser therapy for genitourinary syndrome of menopause in gynecologic cancer survivors. (February 2021) - Quick, Allison M.; Dockter, Travis; Le-Rademacher, Jennifer; Salani, Ritu; Hudson, Catherine; Hundley, Andrew; Terstriep, Shelby; Streicher, Lauren; Faubion, Stephanie; Loprinzi, Charles L.; Coleman, Jenell S.; Wang, Karen C.; et al.
Highlights: This study evaluated the efficacy of fractional CO2 laser treatments in gynecologic cancer survivors with GSM. There were no serious adverse events as a result of laser treatment or sham laser in gynecologic cancer survivors . Fractional CO2 laser treatments appeared to improve sexual function, when compared with sham laser. This study is the first sham controlled study of fractional CO2 laser treatment in gynecologic cancer survivors. Abstract: Purpose: The objectives of this study were to evaluate the feasibility and efficacy of fractional CO2 laser therapy in gynecologic cancer survivors. Methods: This was a pilot, multi-institutional randomized sham-controlled trial of women with gynecologic cancers with dyspareunia and/or vaginal dryness. Participants were randomized to fractional CO2 laser treatment or sham laser treatment. The primary aim was to estimate the proportion of patients who had improvement in symptoms based on the Vaginal Assessment Scale (VAS). Secondary aims included changes in sexual function assessed using the Female Sexual Functioning Index (FSFI) and urinary symptoms assessed using the the Urinary Distress Inventory (UDI-6). Results: Eighteen women participated in the study, ten in the treatment arm and eight in the sham arm. The majority of participants had stage I (n = 11, 61.1 %) or II (n = 3, 16.7 %) endometrial cancer with adenocarcinoma histology (n = 9, 50 %). In total, 15 (83.3 %) of the participants completed all treatments and follow-up visit. There was no difference in the change in the median VAS score from baseline to follow-up. However, there was an improvement in change in the median total FSFI score with treatment compared with sham (Δ 6.5 vs −0.3, p = 0.02). The change in the median UDI-6 score was lower in the treatment arm (Δ −14.6 vs −2.1, p = 0.17), but this was not statistically significant. There were no reported serious adverse events. Conclusions: Fractional CO2 laser therapy is feasible in gynecologic cancer survivors, with preliminary evidence of safety. In addition, there was preliminary evidence of improvement in sexual function compared with sham treatment. Clinicaltrial.gov Identifier: NCT03372720 (OSU-17261; NCI-2017-02051)